Environmentally Mediated Social Dilemmas. (January 2019) - Estrela, Sylvie; Libby, Eric; Van Cleve, Jeremy; Débarre, Florence; Deforet, Maxime; Harcombe, William R.; Peña, Jorge; Brown, Sam P.; Hochberg, Michael E.
Abstract : By consuming and producing environmental resources, organisms inevitably change their habitats. The consequences of such environmental modifications can be detrimental or beneficial not only to the focal organism but also to other organisms sharing the same environment. Social evolution theory has been very influential in studying how social interactions mediated by public 'goods' or 'bads' evolve by emphasizing the role of spatial structure. The environmental dimensions driving these interactions, however, are typically abstracted away. We propose here a new, environment-mediated taxonomy of social behaviors where organisms are categorized by their production or consumption of environmental factors that can help or harm others in the environment. We discuss microbial examples of our classification and highlight the importance of environmental intermediates more generally. Highlights: Organisms modify their environments in ways that can be beneficial or detrimental not only to themselves but also to others sharing the same environment. Such niche-constructing or niche-destroying activities are often due to the production or consumption of environmental factors, such as resources, wastes, or toxins, which ultimately influence the ecology and evolution of social interactions. We present a new, four-way classification of social behaviors where individual behaviors are categorized into producing/consuming an environmental factor, as well as into helping/harming others. Although not immediately obvious, dispersal (the act of moving within a habitat or between habitats) is another mechanism by which organisms modify their environment. An explicit representation of such environmentally mediated interactions is key to capturing realistic system complexity and can reveal some unexpected outcomes in social dilemmas.